Direct fluoroalkylthiolation of indoles with iodofluoroethane enabled by Na2S2O4. Issue 1 (3rd January 2023) - Yu, Nianhua; Huang, Jianjian; Leng, Faqiang
Abstract : A simple and efficient approach for the fluoroalkylthiolation of indoles with iodofluoroethane and Na2 S2 O4 was established. Various fluoroalkylthiolated indoles/2, 3′-biindoles could be produced through this method. Abstract : In this paper, we report an efficient approach for the direct fluoroalkylthiolation of indoles with iodofluoroethane in the presence of Na2 S2 O4 . In this work, we employed readily available iodofluoroethane and Na2 S2 O4 as fluoroalkylthiolation reagents, featuring mild conditions and a wide range of indole substrates. In addition, fluoroalkylthiolated 2, 3′-biindole derivatives can also be prepared by this method.